Determinants for Perinatal Mortality in South China: A Prospective Cohort Study - Liu, Yiping; Li, Qiongxuan; Wang, Tingting; Zhang, Senmao; Chen, Letao; Li, Yihuan; Diao, Jingyi; Li, Jinqi; Song, Xinli; Sun, Mengting; Wei, Jianhui; Shu, Jing; et al. (Frontiers in Pediatrics, 2022)
Abstract Objective: To assessed possible associations between selected maternal and fetal characteristics and perinatal mortality in South China. Methods: A prospective cohort study was conducted in Hunan provincial Maternal and Child Health Care Hospital from March 2013 to December 2019. The exposures of interest were maternal socio-demographic characteristics, abnormal pregnancy history and complications of pregnancy. Their effect in the development of perinatal death were analyzed based on multivariate poisson regression analysis. Crude and adjusted relative risk with 95% confidence intervals were calculated. Results: Of the 44,048 births eligible for data analysis, 596 were identified as perinatal deaths (with mortality rate of 13.5 per 1,000 births). After adjustment for other factors, maternal obesity, employed, history of gestational diabetes mellitus, history of gestational hypertension, history of neonatal death, taking antidepressants in early pregnancy, gestational diabetes mellitus, infertility drug treatment and assisted reproductive techniques, preterm birth and congenital malformations all significantly increased the risk of perinatal death. Ethnic minority, income >5000, multiparous women, and caesarean section associated with reduced risk of perinatal death. Conclusions: Some factors of maternal socio-demographic characteristics, abnormal pregnancy history, lifestyle and habit in early pregnancy and complications of pregnancy were associated with the perinatal death.